(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The genetic variability of Helicoverpa armigera (Hübner) at different agroecological zones of Bangladesh in comparison with Indian population was conducted in India during September 2008 to February 2009. A total of 12 H. armigera populations of which 10 populations collected from different agroecological zones of Bangladesh and two populations from India were tested for their genetic variability. Eight out of the ten primers produced scorable PCR products by amplifying the template DNA with taq polymerase and were subjected for analysis. Those eight primers got amplified to a total of 138 markers which produced polymorphic markers. The similarity coefficient based on 138 RAPD markers ranged from 0.000 to 0.777 of the pair-wise combination among twelve samples of H. armigera. An UPGMA dendrogram based on Jaccards similarity coefficient was constructed for the 12 samples of H. armigera. The dendrogram showed that H. armigera population from Bangladesh had 25 to 45 percent similarity, and in its Indian population the similarity remained within this range. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20428 Bangladesh J. Agril. Res. 39(2): 263-271, June 2014